Reduction in Root Secondary Growth as a Strategy for Phosphorus Acquisition - Strock, Christopher F.; de la Riva, Laurie Morrow; Lynch, Jonathan P. (Plant physiology (Bethesda), 2018)
We tested the hypothesis that reduced root secondary growth of dicotyledonous species improves phosphorus acquisition. Functional-structural modeling in SimRoot indicates that, in common bean (Phaseolus vulgaris), reduced root secondary growth reduces root metabolic costs, increases root length, improves phosphorus capture, and increases shoot biomass in low-phosphorus soil. Observations from the field and greenhouse confirm that, under phosphorus stress, resource allocation is shifted from secondary to primary root growth, genetic variation exists for this response, and reduced secondary growth improves phosphorus capture from low-phosphorus soil. Under low phosphorus in greenhouse mesocosms, genotypes with reduced secondary growth had 39% smaller root cross-sectional area, 60% less root respiration, 27% greater root length, 78% greater shoot phosphorus content, and 68% greater shoot mass than genotypes with advanced secondary growth. In the field under low phosphorus, these genotypes had 43% smaller root cross-sectional area, 32% greater root length, 58% greater shoot phosphorus content, and 80% greater shoot mass than genotypes with advanced secondary growth. Secondary growth eliminated arbuscular mycorrhizal associations as cortical tissue was destroyed. These results support the hypothesis that reduced root secondary growth is an adaptive response to low phosphorus availability and merits investigation as a potential breeding target.